Hyperactivity in the Hypothalamic-Pituitary-Adrenal Axis: An Invisible Killer for Anxiety and/or Depression in Coronary Artherosclerotic Heart Disease - Lan-Shuan Feng; Yi-Ming Wang; Huan Liu; Bo Ning; Hu-Bin Yu; Shi-Lin Li; Yu-Ting Wang; Ming-Jun Zhao; Jing Ma (Journal of Integrative Neuroscience)
The coexistence of anxiety or depression with coronary heart disease (CHD) is a significant clinical challenge in cardiovascular medicine. Recent studies have indicated that hypothalamic-pituitary-adrenal (HPA) axis activity could be a promising focus in understanding and addressing the development of treatments for comorbid CHD and anxiety or depression. The HPA axis helps to regulate the levels of inflammatory factors, thereby reducing oxidative stress damage, promoting platelet activation, and stabilizing gut microbiota, which enhance the survival and regeneration of neurons, endothelial cells, and other cell types, leading to neuroprotective and cardioprotective benefits. This review addresses the relevance of the HPA axis to the cardiovascular and nervous systems, as well as the latest research advancements regarding its mechanisms of action. The discussion includes a detailed function of the HPA axis in regulating the processes mentioned. Above all, it summarizes the therapeutic potential of HPA axis function as a biomarker for coronary atherosclerotic heart disease combined with anxiety or depression.